COVID-19 Mortality Characteristics During First to Third Pandemic Wave in Malang - Dewi Indiastari; Nur Samsu; Didi Candradikusuma; Niniek Budiarti; Heri Sutanto; Siti Fatma (Universitas Brawijaya, 2022)
Background: The epidemic of SARS-CoV-2 has spread worldwide for about one and half years, including in Indonesia, with several peaks in cases and mortality rates. A descriptive pattern of Covid 19 inpatients in Saiful Anwar General Hospital Malang needed to improve health service quality and reduce mortality rates. Aim: Determine the descriptive pattern of inpatients Covid 19 in the internal medicine ward in Saiful Anwar General Hospital from March 2020 until February 2022. Methods: This descriptive study was conducted from March 2020 to July 2021 and used convenience sampling due to sample availability. A total of 137 hospitalized patients in December 2020, 387 in July 2021, and 113 in February 2022 patients were included with information about age, sex, medical diagnosis, comorbid, and outcome, which was obtained from medical records. Descriptive analysis was used to explore frequency distribution and analysis. Results: We found several factors associated with the frequency of SARS-CoV-2 cases. Overall, these results emphasize the role of comorbidity as a possible driver of the COVID‑19 case fatality rate. Conclusion: In the three waves of Covid 19 in Indonesia, the highest case fatality rate was during the Delta variant in July 2021, where more factors significantly affected case mortality.